Clinical and molecular profile of young adults with early‐onset colorectal cancer: Experience from four Australian tertiary centers. Issue 6 (30th January 2022) - Siu, Derrick Ho Wai; Ali, Arwa; Tjokrowidjaja, Angelina; De Silva, Madhawa; Lee, Joanna; Clingan, Philip R.; Aghmesheh, Morteza; Brungs, Daniel; Mapagu, Cristina; Goldstein, David; O'Neill, Siobhan; Liauw, Winston S.; et al.
Abstract: Background: Patients with early‐onset colorectal cancer (EO‐CRC) have unique characteristics. Contemporary data on the pathological and molecular features, and survival of EO‐CRC are limited in the Australian context. Aim: To determine the demographic, histopathological and molecular characteristics of adults with EO‐CRC, and their survival. Methods: We conducted a retrospective study of adults aged 18–49 years with EO‐CRC who were referred to the Illawarra Shoalhaven Local Health District, South Eastern Sydney Local Health District and Royal North Shore Hospital in New South Wales, Australia, between 2014 and 2018. Results: Of 257 patients included, 94 (37%) patients presented with de novo metastatic CRC, 80% patients had near‐average risk family history and 89% had a symptomatic presentation. In 159 patients with nonmetastatic disease at diagnosis, stage III disease (OR 3.88 [95% CI: 1.13–13.3]; p  = .03) and the presence of perineural invasion (PNI) (OR 6.63 [95% CI: 2.21–19.84]; p  = .001) were risk factors associated with the development of metastatic disease. Among 94 patients with de novo metastatic disease, 43 (43%) and 12 (14%) patients harbored a KRAS or BRAF V600E mutation, respectively. The median overall survival was 29.6 months (95% CI: 20.4–38.7). BRAF mutation was associated with inferior survival (HR 3.00 [95% CI: 1.30–6.94]; p  = .01). Conclusion: The prevalence of KRAS and BRAF mutations in our cohort is similar to the overseas experience. Stage III disease at diagnosis, presence of PNI and BRAF mutation are adverse prognostic indicators. A better understanding of the molecular landscape is needed for this patient cohort, so as to better tailor prevention strategies, screening and treatment pathways.